Design of a Robot for the 2019 NASA Robotic Mining Competition - Braccio, Matthew (Proceedings of the Wisconsin Space Conference, 2020)
The viability of extracting water on both the Moon and Mars is a focus of NASA as they explore the idea of In-Situ Resource Utilization (ISRU). Marquette Aerospace and Robotic Systems (MARS) is participating in the 2019 NASA Robotic Mining Competition (RMC), a competition driven by using the systems engineering process to design, build, and test a robot capable of autonomously mining icy-regolith simulant in an off-world terrain to simulate an ISRU mining mission. The team used systems engineering to guide technical management, design, and operations of the robot. With feedback from the team’s faculty advisor and industry sponsors, the team utilized multiple systems engineering approaches. No single systems engineering process was selected, rather the team drew from multiple reference texts. The proposed design satisfies the requirements outlined in the 2019 NASA RMC Rules and Rubrics and placed 6th out of 50 in the competition.